PREVENTING MONEY LAUNDERING THROUGH ILLICIT ENRICHMENT POLICY REGULATORY: AN INDONESIA-MALAYSIA COMPARISON - Arum Roselinda; Yuliati; I Nyoman Nurjaya (CV. RADJA PUBLIKA, 2025)
This research explores the urgency of regulating illicit enrichment within Indonesia’s Money Laundering Law and identifies the ideal evidentiary mechanism to support its enforcement through a comparative analysis with Malaysia. Despite Indonesia’s ratification of the United Nations Convention against Corruption (UNCAC), the absence of explicit provisions on illicit enrichment weakens the country’s capacity to address disproportionate wealth among public officials. Law enforcement remains dependent on proving predicate offenses, which limits asset recovery and the deterrent effect of anti-money laundering efforts. Conversely, Malaysia, through the Malaysian Anti-Corruption Commission Act (MACC Act) 2009, has adopted a more progressive framework that integrates asset declaration, verification of wealth sources, and investigative authority, even without directly criminalizing illicit enrichment. Using a normative juridical approach combined with comparative and case analysis, this research finds that Indonesia requires a hybrid evidentiary model integrating the principles of legal certainty and responsive law. Such a system would establish clear statutory standards, an asset forfeiture framework, and adaptive mechanisms that enhance transparency, public participation, and accountability. Strengthening Indonesia’s anti-money laundering regime through the integration of illicit enrichment provisions would not only ensure early detection of unexplained wealth but also advance asset recovery and institutional integrity.